Optimization and in vivo evaluation of quetiapine-loaded transdermal drug delivery system for the treatment of schizophrenia. (1st November 2020) - Agrawal, Milan B.; Patel, Mayur M.
Abstract: The prevailing studies were carried out to formulate and optimize the quetiapine transdermal matrix patch by the usage of Box–Behnken design for ameliorated bioavailability when contrasted with conventional drug delivery. The Box–Behnken design with three-level and three-factor was utilized to explore the intermingle impact of critical attributes on tensile strength, in vitro drug release, and flux. Optimized formulation was characterized for Fourier transform infrared, differential scanning calorimetry, in vivo pharmacokinetics, and skin irritation along with stability studies. The inference of the finalized batch (F14 ) depicted the flux of 51.81 ± 0.32 µg/h/cm 2, TS of 6.46 ± 0.56 MPa, and the % drug release after 20 h of 82.98 ± 1.48% with no remarkable variation even after 6 months stability studies. Correlation between predicted and the observed values of the dependent variables was very closer. Optimized quetiapine transdermal patch did not exert any symptoms of skin irritation. The bioavailability of quetiapine was enhanced almost 4.59 times after topical delivery when contrasted with the conventional dosage form. The outputs of the research work divulged that the developed matrix patch of quetiapine for transdermal drug delivery can be a propitious opportunity that affords effective treatment of schizophrenia. Novelty statement: The oral route is not suitable for the drugs having extensive first-pass metabolism which leads to reduced bioavailability. For the parenteral route, invasiveness causes the patient noncompliance while sterility contributes to the cost factor. Moreover, the treatment of schizophrenic patients is a challenging task for caregivers and doctors. Hence, the transdermal patch of quetiapine was developed to bypass the biotransformation of drugs and thereby to enhance the bioavailability as well as to provide sustained drug delivery which ultimately reduces the dosage frequency.